ENHANCEMENT OF THE QUALITY OF HUMAN RESOURCES THROUGH TRAINING AND DEVELOPMENT PROGRAMS IN SCHOOLS - Charlita Trihapsari; Fadhilah Mujahidah; Neneng Humairoh (JURNAL AL-TANZIM, 2021)
This study aims to analyze and understand the training and development program carried out by SMP YAMIS Jakarta in improving the quality of its human resources. This research uses a qualitative case study approach. The data collection technique is done through interviews, observation, and documentation. Data analysis is done through data presentation, data reduction, and concluding. The results showed that the training and development program carried out by SMP YAMIS Jakarta in improving the quality of its human resources was through the Subject Teacher Consultation (MGMP) activities which were carried out periodically by the existing schedule, involving teachers in seminars on learning methods that creative, innovative and fun, holding independent training in schools by inviting resource persons who are experts in the field, and programmed supervision carried out by school principals to employees regarding the achievement of planned educational goals.